Efektivitas UU ITE dalam Menangani Penyebaran Konten Pornografi di Twitter/X - Amanda Mellyuana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the effectiveness of the Electronic Information and Transactions Law (UU ITE) in addressing the dissemination of pornographic content on Twitter/X. Using a literature review approach, it highlights UU ITE’s role in regulating digital activities by prohibiting the distribution of obscene content. Despite providing a robust legal framework, its implementation faces significant challenges, including user anonymity and limited monitoring capabilities. Data from the Ministry of Communication and Informatics (Kominfo) reveals a substantial increase in the number of blocked pornographic content, although it represents only a fraction of the broader issue. Additionally, Twitter/X’s content moderation policies often conflict with local regulations, requiring closer collaboration between governments and digital platforms. Potential solutions include adopting artificial intelligence for automatic detection, enhancing user verification, and fostering international cooperation. This study concludes that synergy between the government, digital platforms, and the public is essential for creating a safer and more conducive digital space.